PTH-003 Fully Covered Self Expanding Metals Stents Are Effective In Remodelling Benign Biliary Strictures In Patients With Chronic Pancreatitis. (9th June 2014) - Paranandi, B; Joshi, D; El-Sayed, GH; Patel, P; Chapman, MH; Pereira, SP; Webster, GJ; Johnson, GJ
Abstract : Introduction: Symptomatic benign biliary strictures (BBS) in chronic pancreatitis (CP) have historically been treated with surgical biliary bypass or multiple plastic stents. We report our experience of fully covered self-expanding metal stents (fcSEMS) for this indication in a cohort of patients with CP. Methods: A prospectively recorded ERCP database including all CP patients undergoing fcSEMS for BBS, between Oct 2008 and Aug 2013, was analysed. Demographics, pathology results, stent data and patient outcomes were collated. Results: A total of 256 ERCPs involving biliary SEMS insertion were performed of which 115 (45%) were fcSEMS. 48/115 (42%) fcSEMS were performed in 24 patients (75% Male, median age 55 years) with BBS related to CP. Aetiological factors included alcohol (63%), autoimmune (13%) and idiopathic (8%). Surgical bypass was precluded in 23/24 (96%) patients due to extensive choledochal varices (58%), advanced cirrhosis (13%), medical comorbidities (13%), hostile surgical abdomen (13%) and autoimmune CP (13%). 17/24 (71%) patients had previous plastic biliary stent (s). 10mm diameter fcSEMS (Boston Wallflex or Cook Evolution) of 6 or 8 cm in length were used. They remained in situ for median 9.5 months (range 1–32). 13/24 (54%) patients achieved stricture remodelling, allowing trial of fcSEMS removal and follow up without stenting for median 7 months (range 0–22). These patients required median 3 fcSEMS (range 1–6) over median 24 months (range 2–51) to achieve stricture resolution. 42% (10/24) patients who had not yet achieved stricture resolution had fewer fcSEMS to date (median 1) and a shorter duration of stenting. Complications included proximal (4%) and distal stent migration (16.5%), cholecystitis (6%) and acute pancreatitis (2%). Biliary obstruction +/- cholangitis occurred in 23% at some point. 96% (46/48) fcSEMS were easily removed without needing additional procedures. One fcSEMS was in situ for 18 months (patient lost to follow up) and it was not possible to then remove it (due to tissue in-growth). Another fcSEMS in situ for 32 months (due to tissue in-growth) was removed following a "stent-in-stent" fcSEMS procedure. 2 patients died before planned removal of their first metal stent due to pre-existing comorbidity. Conclusion: As suggested by smaller published series (Kaffes, GI Endoscopy 2013), FcSEMS are a safe and effective approach to managing BBS due to CP and may promote stricture remodelling. Endoscopic removal is straightforward if the fcSEMS is in situ for <12 months. Disclosure of Interest: None Declared.